呼吸同期放射線治療の改良に向けた内臓変位の解析 - 樋口, 雅則; 山本, 隆夫; 土橋, 敏明; 太田, 直哉; 岡村, 英希; 江原, 威; 槇, 靖幸 (Nihon Reoroji Gakkaishi, 2016)
We have analyzed a displacement of lung tissues induced by aspiration and expressed it by a phenomenologically derived ellipsoidal harmonics for time course of craniocaudal displacement for a cycle of aspiration. A fitting of the equation to 4DCT images for a pair of lung of five individuals was used for the analysis of the displacement. The observed data were fitted well to the phenomenological equation. The positional dependence of the fitting parameters was reasonably explained. It is suggested that the parameter that denotes the width of the expiration phase could be used to evaluate the validation of the respiratory-gated imaging technique in irradiation therapy for each patient.